1995
DOI: 10.1093/oxfordjournals.aje.a117418
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Parental Smoking on the Prevalence of Wheezing Respiratory Illness in Children

Abstract: To quantitatively assess environmental tobacco smoke exposure from parental smoking as a risk factor for asthma or wheezing in childhood, and to derive estimates of excess asthma/wheezing lower respiratory tract illness cases attributable to this risk factor, a cross-sectional analysis of the 1987 National Medical Expenditure Survey (a national probability sample of the civilian, noninstitutionalized US population) was undertaken. The National Medical Expenditure Survey included 7,578 children and youth less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
1
7

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(75 citation statements)
references
References 0 publications
2
65
1
7
Order By: Relevance
“…Multiple studies have reported that children exposed to ETS are at risk for developing lower lung function, increased use of rescue medications, and more frequent hospitalizations (15,16,31). As reported in RESULTS, averaged albuterol usage and LTE 4 levels were higher on days with higher cotinine levels but the effect of subsequent ambient pollutant concentrations was attenuated.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Multiple studies have reported that children exposed to ETS are at risk for developing lower lung function, increased use of rescue medications, and more frequent hospitalizations (15,16,31). As reported in RESULTS, averaged albuterol usage and LTE 4 levels were higher on days with higher cotinine levels but the effect of subsequent ambient pollutant concentrations was attenuated.…”
Section: Discussionmentioning
confidence: 81%
“…Almost all such studies estimate ambient health effects without taking into account concurrent exposures that may impact asthma, such as environmental tobacco smoke (ETS). However, in the setting of urban asthma, where high ambient exposures are assumed, concurrent exposures to ETS are also prevalent (13)(14)(15)(16)(17)(18)(19)(20). There are limited data on the response to ambient or indoor exposures in the typical urban environment where these concurrent exposures often occur.…”
mentioning
confidence: 99%
“…A 25-item questionnaire was developed from existing instruments (Chilmoncyzk et al, 1993;American Institute of Research, 1991;Asher et al, 1995;New York City Health and Hospitals Corp., 1995;Beckett et al, 1996;Koren, 1997;Eskenazi et al, 1999;Joseph et al, 1999) and was designed to characterize symptoms, health practices, and environmental exposure factors that have been documented to be asthma triggers or suspected asthma triggers (Chilmoncyzk et al, 1993;Ingram et al, 1995;Stoddard and Miller, 1995;Beckett et al, 1996;Koren, 1997;Platts-Mills and Carter, 1997;Eskenazi et al, 1999). Parents were requested to complete the questions (in either Spanish or English) about their child's respiratory health (symptoms, diagnosis, and medications), family history of asthma, school absenteeism, potential environmental exposures in the home, insurance status, and race/ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…O aleitamento natural é considerado um fator protetor contra a infecção respiratória aguda 6 , e entre os fatores de risco incluem-se: a ventilação do domicílio, o estado nutricional da criança, o nível de escolaridade dos pais, a densidade domiciliar e o tabagismo dos moradores da casa, principalmente o da mãe 7,8 .…”
Section: Introductionunclassified